Bio-electrosynthesis of polyhydroxybutyrate and surfactants in microbial fuel cells: a preliminary study - Nastro, Rosa Anna; Kuppam, Chandrasekhar; Toscanesi, Maria; Trifuoggi, Marco; Pietrelli, Andrea; Pasquale, Vincenzo; Avignone-Rossa, Claudio (Frontiers in Microbiology, 2025)
Microbial Electrochemical Technology (MET) offers a promising avenue for CO2 utilization by leveraging the ability of chemolithotrophic microorganisms to use inorganic carbon in biosynthetic processes. By harnessing the power of electroactive bacteria, METs can facilitate the conversion of inorganic carbon into organic compounds. Therefore, this work combines biosurfactant production at the anode and PHB production at the cathode of Microbial Fuel Cells (MFCs), while testing the efficiency of Microbial Electrosynthesis Cells (MECs), and traditional culture in liquid media. This study employed a consortium of Pseudomonas aeruginosa PA1430/CO1 and Shewanella oneidensis MR-1, to provide reducing equivalents to Cupriavidus necator DSM428 for CO2 fixation and polyhydroxybutyrate (PHB) production. Glycerol was used as a carbon source by the anode consortium to investigate biosurfactant production. Additionally, Adaptive Laboratory Evolution (ALE) was employed to enhance the efficiency of this process to develop biofilms capable of synthesizing PHB from CO2 in MFCs under a controlled gas atmosphere (10% CO2, 10% O2, 2% H2, 78% N2). Observed results showed a higher direct CO2 removal from the gas mix in MECs (73%) than in MFCs (65%) compared to control cultures. Anionic (18.8 mg/L) and non-ionic (14.6 mg/L) surfactants were primarily present at the anodes of MFCs. Confocal microscope analysis revealed that the accumulation of PHBs in C. necator was significantly higher in MFCs (73% of cell volume) rather than in MECs (23%) and control cultures (40%). Further analyses on metabolites in the different systems are ongoing. Our data gave evidence that the anode consortium was able to provide enough electrons to sustain the chemolithotrophic growth of C. necator and the biosynthesis of PHBs at the cathode of MFCs, in a mechanism suggestive of the direct interspecies electron transfer (DIET), naturally occurring in natural environment.